Peran Peran Pemerintah Desa dalam Tata Kelola Program Hutan Kemasyarakatan (HKm) Desa Londerang - Rianti Simanjuntak; Michael Lega; Fajar Alan Syahrier (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
The Community Forestry Program (HKm) aims to empower communities around forest areas through sustainable forest management while improving local welfare. However, in Londerang Village, Kumpeh District, the program faces challenges, particularly regarding the limited attention from village government in managing the Bumi Indah Sejahtera Farmer Group Association (KTH). This study examines the role of village government in HKm governance using qualitative methods with a case study approach. Data were collected through in-depth interviews with village officials, KTH members, community representatives, and UPTD KPHP XIII Muaro Jambi, complemented by observation and document analysis. The findings reveal that village government plays four key roles based on Ryaas Rasyid's theory: as regulator through policy formulation and supervision, as dynamizer by encouraging community participation and resolving conflicts, as facilitator by providing access to permits and infrastructure, and as catalyst by initiating program development and innovation. However, coordination between village government and KTH remains suboptimal, limiting program effectiveness. This research contributes to understanding local governance in natural resource management and provides practical recommendations for strengthening village government capacity in implementing community-based forestry programs.